Qualitative Study on the Dynamics of Social Interaction Between Boarding Students and the Local Community - Deny Hadi Siswanto; Wahyu Ari Wibowo; Yohan Dwi Saputra; Ramadhan Rifana Rozaq; Handika Suryatama; Surya Adi Saputra (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to examine the social behavior of boarding (kost) students towards the community in Ngestiharjo Village. Using a qualitative method and involving 10 informants, the study reveals that the social behavior of students is influenced by differences in ethnicity, race, and religion. When supervision is lacking, students tend to exhibit deviant behavior, particularly due to the boarding environment’s insufficient attention to their activities. In addition to their behavior in the boarding area, students often seek an escape outside the campus to overcome boredom and experience freedom. These findings highlight the importance of better management and supervision of the boarding environment to minimize deviant behavior and enhance positive interactions between students and the local community